Primary School Students' Attitudes toward Plants - Kaplan, Kubra; Topsakal, Unsal Umdu (ELSEVIER SCIENCE BV, 2013)
The purpose of research is to investigate the students' attitudes toward plants and how influence gender and socioeconomic status to these attitudes. The data gathered from 40 6th grade students in Istanbul. In this study qualitative research method is used. A survey instrument that includes open-ended questions was applied and semi-structured interviews are made. As a consequence of this research, it has been revealed that 6th grade students have positive attitudes towards plants by accepting it as living thing and the difference in gender and socioeconomic status do not influence attitudes toward plants. (C) 2013 The Authors. Published by Elsevier Ltd. Open access under CC BY-NC-ND license.
Keywords: Attitudes toward plant; science education; pommy education; Education & Educational Research